Investigating the Balassa-Samuelson hypothesis in transition: Do we understand what we see? - Balázs Égert (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
This paper studies the Balassa-Samuelson effect in the Czech Republic, Hungary, Poland, Slovakia and Slovenia.Time series and panel co-integration techniques are used to show that the BS effect works reasonably well in these transition economies during the period 1991:Ql to 2001:Q2.However, productivity growth does not fully translate into price increases due to the structure of CPI indexes.We thus argue that productivity growth will not hinder the ability of the five EU accession candidates to meet the Maastricht criterion on inflation in the medium term.Moreover, the observed appreciation of the CPI-deflated real exchange rate is found to be systematically higher compared to the real appreciation justified by the Balassa-Samuelson effect, particularly in the cases of the Czech Republic and Slovakia.This may be partly explained by the trend appreciation of the tradable-goodsprice-based real exchange rate, increases in non-tradable sector prices due to price liberalisation and demand-side pressures, and the evolution of the nominal exchange rate due to the exchange rate regime and magnitude of capital inflows.
URN:NBN:fi:bof-201408072090
Keywords: 330